TRANSFER PRICING IN THE PERSPECTIVE OF INTERNATIONAL BUSINESS LAW AND ETHICS - Mahrum Maini; Noorzilah; Taufik Ismail Harahap; Yeltriana; Ismed Batubara (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Transfer Pricing is currently widely carried out by multinational companies with the aim of avoiding taxes because the company wants a large amount of profit, Tax avoidance activities result in bad risks for the company related to the company's reputation in the wider community but in fact taxes are very important income in the country, because the tax revenue is used to finance all forms of national development for the welfare of the people. This research is motivated by government complaints about transfer pricing actions carried out by multinational manufacturing companies or other large companies which are considered very contrary to the state system of the Republic of Indonesia, The formulation of the problem in this study is how the process of transfer pricing occurs and its relationship to state revenues to the tax sector in Indonesia and how according to the views of international business law and ethics related to the application of transfer pricing in a company. This research is an empirical juridical research with a descriptive analytical approach.